Innovative education: Virtual labs - Zotou, Elissavet Spyridoula (Open Schools Journal for Open Science, 2018)
What can we do to improve our system of education, our society and our future? Virtual labs can become an inseparable part of every student’s life. The aim of this article is to inform as more students and teachers as possible about this new way of teaching and learning, what it has to offer, if it is used abroad, in what ways it can be used and under what certain circumstances.